Kejadian keloid menurut golongan darah pada pasien pasca Iuka di Rumah Sakit Umum Pusat H. Adam Malik Medan - Said Fuadi; Frank Bietra Buchari; Utama A.Tarigan (Majalah Kedokteran Nusantara The Journal Of Medical School, 2015)
Introduction :Keloid is a manifestation of wound healing with imbalance syntesize and collagen degradation. Abnormal scar will grow through to the edge of wound then feeling itchy and needle-like pain. The common cause of keloid is continously overproduced of collagen, remodelling defect in cells and extracelluler matrix, overform of infiltration cells, and deficit of elastic tissue due to increase of fibroblast metabolic activity. Keloid has component which contain collagen, fibronectin and glycosaminoglycan. Of all lession, N-acetylgalactosamine is the most common glycosaminoglycan. Antigen A contain a N acetylgalactosaminyttransferase which form of blood type A and AB. Objective :The aim of the study to determine blood types which have keloid risk post wound at RSUP H.Adam Malik Medan. Method :This study was a descripnve study which descripted the phenomenon included risk factor , effect, or result. This study used 33 people as sample, that represented post-wound keloid patients at Plastic Surgery Clinic H.Adam Malik Hospital. Data was collected by blood type from anamnesis or finger prick method. Result : In this study blood type B was the most common keloid post-wound with 54.5% and blood type A 24.2%, blood type 0 12.1% and blood type AB 9.1%. Conclusion : In this study blood type B was the most common keloid post-wound with 54.5%. Keywords : keloid, Finger Prick Method, blood type